MISI BUDAYA MIGRAN ETNIK SASAK DI KECAMATAN DENPASAR TIMUR KOTA DENPASAR SEBUAH : KAJIAN BUDAYA - Sudiarta, I Nengah (PIRAMIDA, 2012)
The difficulty of undertaking at an origin region or a former village push thesociety conducting a citizen movement known as migration or urbanization. Thecity of Denpasar as a tourism destination, the economical fluctuationautomatically increases very fast and it has some impacts to the income per capitafor the around society. So the city of Denpasar is a region becoming a migrants’destination to speculate their destiny or they want to change their family income.Instead of a such situation, Denpasar city will generate the citizen’s increasingvery rapid. The heterogeneous citizen have a potency of ethnical conflict, thetraffic jam, slump housing and so on. The sharing life of some ethnics will occur acultural contact of any kinds origin village and each ethnic wants to reflect theirprevious culture at a new area especially regarding to the cycle life rite.The questions research are : (i) what is the migrants’ cultural mission formof Sasak ethnic at East Denpasar sub district, (ii) what is the migrants’ culturalmission function of Sasak ethnic at East Denpasar sub district, (iii) what is themigrants’ cultural mission meaning of Sasak ethnic at East Denpasar sub district.The research is designed by using the qualitative analysis and the collectingdata is done by using the observation technique, an interview, a discussion groupfocus and a documentation. In analyzing data, researcher uses the culturalconfiguration theory, the symbolic interaction, the change theory, the adaptiontheory and the other supporting one.The research results show that : Firstly, the migrants reflect their previouscultural form at a new place related to the life cycle rite. It’s done regarding thereis a such of an ethnical pride because they want to be recognized their existenceat the destination region, Secondly, After Ethnical migrants of Sasak succeeded atthe destination region, they want to maintain their identity at the new environmentwith the others ethnic and they also want to spread to a strategic area to coverthe economical sector. In other to cover safely, they need adapting andharmonizing with the other ethnic especially the dominant original one. So themigrants’ cultural mission of Sasak ethnic at East Denpasar sub district wantto bring their operating result as much as possible, such as their remittance andexperience to the former region. By the shoreline mental of discipline and ductilenature, they work as effective as possible. Thirdly, Meaning of the mission is toincrease their family life prosperity and help progressing the small economic atoriginal village, help developing the general facilities and try harmonizing withtheir environmental requirement.The conclusions are : by conducting the migrants’ cultural mission of Sasakethnic, they can change their social-economical life toward to a better one, andalso reflect their social-culture at new setting up destination
Keywords: the cultural mission, reflect social cultural, prosperity and identity strengthening